Artificial neural systems: future business connection. (4th August 2014) - Bergman, R.; Cardinali, R.
The human brain is the most complex organ in the human body. Two major components which account for its complexity are synapses and neurons. Synapses are the communication links between neurons. Synapses also serve as gateways that allow only signals of a certain strength to pass from neuron to neuron. Neurons, the control unit of the brain, collect inputs to be transformed into outputs. This process can be compared somewhat to the function of the processor in a computer. But the brain, unlike a computer, can make decisions based on pattern recognition rather than repetition data processing. Artificial Neural Systems (ANS) seek to imitate the brain's processing function. ANS research encompasses a number of scientific fields. Included in the field are physiology, biology, engineering, psychology, physics, and mathematics. To date little research has been conducted in the utilisation of ANS technology in the business environment. The expertise required to apply ANS techniques to solve business problems lies with system analysts, computer scientists and management information specialists. The purpose of this paper is to examine how the integration of ANS technology to business can be utilised.